Rectangular Emotion: The Expression of Awe in Painting and the Wolfe Creek Meteorite Crater - Robertson, Kevin John (Curtin University, 2017)
This project studies the practical and theoretical expression of awe in contemporary painting. Works by Sidney Nolan and Mamma Andersson provide a backdrop to this investigation. The Wolfe Creek Meteorite Crater was selected as a subject from which to translate the experience of awe into large scale works painted on site. An original methodology was developed that combines Deleuzian affect theory with theories of representation, resulting in an affective trans-representational model of expressive painting.